2002
DOI: 10.1162/152039702320201085
|View full text |Cite
|
Sign up to set email alerts
|

Hollywood Glamour and Mass Consumption in Postwar Italy

Abstract: Italian society after World War II was profoundly affected by the culture of “glamour” that encouraged mass consumption. This culture drew heavily on images and desires created by the American film industry, and it would not have arisen in the absence of American glamour. Over time, however, Italian glamour acquired some important indigenous features, which were economically beneficial for Italy in boosting exports and tourism. Through most of the Cold War, the perceived glamour of Rome captured in the film La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 3 publications
0
15
0
5
Order By: Relevance
“…Research on film tourism can be found since the early 1990s [29]. Only a decade ago, it was noted that there is a lack of academic research in film-induced tourism [4,30], but the popularity and extensiveness of research in this part has increased recently [31,32], with most researches investigating the growth of visitor numbers to film sites [33][34][35][36][37][38][39][40][41]. But practical studies measuring the impact of films on the behavioral characteristics of the watchers in relation to a specific destination are scarce, and understanding of the cultural implications pertinent to film-induced tourism is limited [4,42].…”
Section: Studies Of Film Induced Tourismmentioning
confidence: 99%
“…Research on film tourism can be found since the early 1990s [29]. Only a decade ago, it was noted that there is a lack of academic research in film-induced tourism [4,30], but the popularity and extensiveness of research in this part has increased recently [31,32], with most researches investigating the growth of visitor numbers to film sites [33][34][35][36][37][38][39][40][41]. But practical studies measuring the impact of films on the behavioral characteristics of the watchers in relation to a specific destination are scarce, and understanding of the cultural implications pertinent to film-induced tourism is limited [4,42].…”
Section: Studies Of Film Induced Tourismmentioning
confidence: 99%
“…Toutefois, il faudra attendre la montée du mouvement vert des années 1970 et l'enthousiasme renouvelé du public pour les environnements naturels pour voir les fans s'en aller à la conquête des paysages utilisés dans les films. S'il est vrai que le cinéma produit à l'occasion des films où les personnages doivent partager le rôle titre avec la beauté des panoramas naturels (Never Cry Wolf, 1983 ;Highlander, 1986 ;The Bear, 1989 ;Dances With Wolves, 1990 ;White Fang, 1991 ;The Lord of the Rings, 2001, 2002, 2003etc. ), encore faut-il que le film atteigne un statut icône pour que ses adeptes se transforment en touristes.…”
Section: On Locationunclassified
“…Dans les années 1960, le film La Dolve Vita (1960) a eu l'effet de modifier l'image de la ville jusque-là associée inévitable-ment à la moralité du Vatican. Les personnages campés par Elizabeth Taylor, Ava Gardner et Frank Sinatra, et le recours aux cabarets et boîtes de nuit ont permis de modifier l'image de Rome en l'associant à l'élégance et au luxe mais aussi au plaisir et au péché, et ce, encore aujourd'hui (Gundle, 2002).…”
Section: Les Retombées Et La Gestion Du Ciné-tourismeunclassified
“…The actress herself, apparently detested her more sexy starlet image in Bitter Rice and worked hard to obtain (and maintain) the new svelte look that had been studied especially for her. 36 She even forbade any images associated with this film to be on display in her home. 37 In the transformation of Silvana Mangano and Lucia Bosè, therefore, there is something very revealing: it is the difference between the body being exhibited as an erotic object for all to see and the replacement of that body by a fashioned silhouette.…”
Section: Aristocratic Influences and European Glamourmentioning
confidence: 99%